(untitled) (International journal of artificial intelligence, 2024)
In this paper, we explore the themes of multiculturalism and cultural mixing in the works of Abdulrazaq Gurnakh, one of the most renowned contemporary writers. Issues of identity, migration, and the intersection of different cultures can be seen in many of Gurnakh’s narratives. Through the experiences of his characters, he highlights the tensions and synergies that arise in multicultural environments, particularly in postcolonial contexts. The analysis shows how Gurnakh’s fiction reflects cultural fluidity, demonstrating both the challenges and enrichments that diversity brings to personal and collective identity. An examination of key texts reveals the nuances of Gurnakh’s depiction of cultural convergence and how his work contributes to wider debates about globalization and heritage.